Antioxidant and non-specific immune defenses in partially freeze-tolerant Xizang plateau frogs, Nanorana parkeri. (December 2021) - Niu, Yonggang; Zhang, Xuejing; Zhang, Haiying; Xu, Tisen; Men, Shengkang; Storey, Kenneth B.; Chen, Qiang
Abstract: The Xizang plateau frog Nanorana parkeri can tolerate brief and partial freezing of their body. To determine the significant role of antioxidant defense and non-specific immune defense in freezing survival of this species, we assayed parameters of oxidative damage, antioxidant defense and non-specific immune enzymes during freezing exposure (−2 °C for 12 h) in five organs (heart, brain, liver, kidney, and skeletal muscle). The results showed that freezing led to a significant rise in the content of malondialdehyde (MDA) and carbonyl groups (CG) in brain, liver and kidney tissues. The activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) increased significantly in brain and liver tissues with an augmentation of total antioxidant capacity (T-AOC). Apparent increments in muscle SOD activity and liver GST activity were also observed during freezing exposure. Vitamin C content significantly decreased in liver and kidney but a significant increase occurred in brain. Activities of non-specific immune enzymes, acid phosphatase (ACP) and alkaline phosphatase (AKP), were also assessed. ACP activity was significantly reduced in all five tissues tested whereas AKP activity decreased significantly in four tissues but rose in brain. In summary, freezing is accompanied by oxidative stress in the high-altitude frog, N. parkeri, as documented by increases in the content of MDA and CG in tissues. Freezing exposure also induced tissue-speciﬁc changes in the antioxidant defenses showing that activation of antioxidant systems is a part of the survival strategy of this in a high-altitude frog during freezing. Such up-regulation of antioxidant enzymes suggests a particularly important role for them in the liver and brain, serving as an anticipatory mechanism to deal with the ROS challenge during freeze/thaw episodes. Our findings contribute to extending the current understanding of the mechanisms of freeze tolerance in high-altitude frogs. Highlights: Freezing exposure induced oxidative stress in the high-altitude frog, Nanorana parkeri. Freezing exposure induced oxidative damage in brain, liver and kidney tissues. The activities of SOD, CAT and GPX and T-AOC increased significantly in brain and liver tissues after freezing exposure. ACP and AKP activities reduced significantly in all tissues except brain after freezing exposure.